(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify Cyber Dating Violence among female students in the Department of Psychological Counseling and Educational Guidance. It also aims to identify the significance of differences in Cyber Dating Violence according to the relationship variable (current relationship - previous relationship) and according to the variable of academic level (first, second, third, fourth). It also aims to identify psychological resilience. It also aims to identify the significance of differences in psychological resilience according to the relationship variable (current relationship - previous relationship) and according to the variable of academic level (first, second, third, fourth). It also aims to identify the correlation between Cyber Dating Violence and psychological resilience. To achieve the research objectives, the researcher adopted the Watkins et al. (2018) Cyber Dating Violence Scale, which consists of (17) items. The Connor and Davidson (2003) Psychological Resilience Scale, consisting of (25) items, was used after translating the two scales and verifying the translation validity and psychometric properties. The scales were then applied to a sample of (128) female students. The researcher reached a number of results, including: The research sample was exposed to low levels of Cyber Dating Violence. There was a difference in Cyber Dating Violence, in favor of students who were in a previous relationship. There was a difference between the four stages of Cyber Dating Violence, in favor of fourth-year students. The research sample also possessed high levels of psychological resilience. There was no difference in psychological resilience between students who were in a current and previous relationship. There was no difference between the four stages of psychological resilience. There was a statistically significant inverse relationship between Cyber Dating Violence and psychological resilience. In light of the results, the researcher made a number of recommendations and proposals.